(untitled) (INTERNATIONAL CONFERENCE ON ADVANCE SCIENCE AND TECHNOLOGY, 2025)
This article provides a comprehensive analysis of the pragmatic issues encountered when translating ethnographisms from Uzbek into English, focusing on literary texts as the primary area of exploration. Ethnographisms—words and expressions that reflect a nation’s unique customs, social practices, and cultural traditions—are deeply embedded in the linguistic and cultural fabric of a society. They play a pivotal role in conveying the identity and worldview of a particular ethnic group. However, translating such culturally loaded terms poses significant difficulties due to disparities in cultural background, context, and the pragmatic functions of language in different societies. Literary texts, in particular, require a nuanced approach to translation because they do not merely communicate information but also convey the cultural atmosphere, emotional undertones, and aesthetic values of the original work. The challenge lies in transferring these cultural meanings into the target language without losing the authenticity or emotional resonance of the source. The article investigates various strategies that can be employed to maintain pragmatic equivalence—ensuring that the translated term or expression evokes a similar response or understanding in the target audience. Such strategies include descriptive translation, cultural substitution, footnoting, and the use of transliteration when necessary. Ultimately, the study underlines the importance of the translator’s cultural competence and sensitivity to context in preserving the integrity of the source text while making it accessible and meaningful to the target audience.